Study Of Effluent Water Quality Index From Pig Farming Area In Kampung Selamat, Pulau Pinang - Johari, Aida Syazwani (Universiti Sains Malaysia, 2021)
Pig farming is one of the vital livestock farming in the world. Pig farms produce effluents that are high in Ammonia Nitrogen, BOD, COD and SS. Untreated pig farm effluents are hazardous as they can cause the parameters mentioned to be very high and cause environmental problems. Pig farming pollution studies are rare in Malaysia as pork demand is not high compared to beef and poultry. However, in Malaysia, the research regarding this activity and the characterisation of pig farming effluent does not garner much public attention even though it is one of the biggest pollution concerns. The purpose of this study is to investigate the source of pollution Sungai Kereh that shows pollution inventory comes from Kampung Selamat. This study can be a reference for future studies regarding pig farming pollution that has been a concern these days. The method used for this study is by using WQI and Effluent Discharge Standards issued by the Department of Environment Malaysia. This method mainly focused on the BOD, COD, DO, SS, AN and pH of the effluent and Sungai Kereh. Laboratory tests determined the parameters according to APHA standard methods. This study shows that all the pig farms discharged effluents within the maximum permissible value for Standard B of Effluent Discharge Standard of Sewage (2009) except for SS and AN values where P2 and P3 exceed the maximum permitted value of 50 mg/L with 104 and 131 mg/L respectively for SS. Next, for AN value, only P3 and P4 exceed the maximum value of 50 mg/L with values of 123.92 and 104.58 mg/L accordingly. For the WQI of Sungai Kereh, SK2b, SK2c and SK4 falls into class III and SK1, SK2a and SK3 falls into class IV. Through this WQI and effluent standard, the level of pollution can be determined and check whether the effluent discharged complies with the standard.